Keberadaan Hakim Komisaris dan Transparansi dalam Proses Penyidikan (the existence of judge commissioner And the transparency of the process of investigation) - Muhaimin Muhaimin (Jurnal Penelitian Hukum De Jure, 2016)
Criminal Procedure Code in the document asserted that the defendant-formation-convict defendant as a "Seeker of Justice", then the suspect-defendant-convict get the attention and protection of the law by setting the portion of his or her rights are quite large. Criminal Procedure Code can be considered as an oriented arrangement of substance abusers. Over ± 30 years KUHAP rights owned by the perpetrator, especially during the last 10 years, little by little reduced by the law governing criminal procedure in the legislation spread outside the Penal Code. The arrangement does not mean deprivation of the rights of the suspect-defendant-convict who had been there before, but the reduction of quality in the implementation or fulfillment of their legal rights in such a way that essentially contrary to the philosophy underlying the establishment of legal norms in the Code of Criminal Procedure or the laws in the context of political conflict granting legal protection to suspects, accused-convict. Therefore, there should be firmness in the draft Law on Criminal Procedure that the formation of the new Code of Criminal Procedure did not reduce or remove the least the rights of suspects, defendants, and convicts who have been published in the Code of Criminal Procedure, on the contrary the Draft Law on the Law of Criminal Procedure in fact strengthen it with more concrete legal instruments and easy to apply.Keywords: Judge Commisioner, Supervision, InspectionABSTRAKDokumen KUHAP menegaskan bahwa terdakwa-narapidana sebagai "Pencari Keadilan", maka tersangka-terdakwa-narapidana mendapatkan porsi perhatian dan perlindungan hukum dengan menetapkan bagian hak yang cukup besar. KUHAP dapat dianggap sebagai suatu pengaturan untuk pelaku substansi. Selama ± 30 tahun hak KUHAP yang dimiliki oleh pelaku, terutama selama 10 tahun terakhir, sedikit demi sedikit dikurangi dengan hukum yang mengatur acara pidana dalam perundang-undangan yang tersebar di luar KUHP. Pengaturan ini tidaklah berarti perampasan hak-hak tersangka-terdakwa-narapidana yang sudah ada sebelumnya, tapi pengurangan kualitas dalam penerapan atau pemenuhan hak-hak hukum mereka sedemikian rupa yang pada dasarnya bertentangan dengan filosofi yang mendasari pembentukan norma hukum dalam KUHAP atau hukum dalam konteks konflik politik pemberian perlindungan hukum untuk tersangka-terdakwa-narapidana. Oleh karena itu, harus ada ketegasan dalam draft UU Acara Pidana bahwa pembentukan Kode baru Acara Pidana tidak mengurangi atau menghapus setidaknya hak-hak tersangka, terdakwa, dan narapidana yang telah diterbitkan dalam KUHAP, Sebaliknya, RUU tentang Hukum Acara Pidana, pada kenyataannya, memperkuatnya dengan instrumen hukum yang lebih konkret dan mudah diterapkan.Kata Kunci: Hakim Komisaris; Pengawasan; Pemeriksaan